Naturaleza del contacto entre el Muschelkalk Inferior y el Muschelkalk Medio de la zona de Aiguafre da (Provincia de Barcelona). - Anadón Monzón, P.; Esteban Cerdá, M.; Marzo Carpio, M.; Pomar Goma, L. (Cuadernos de Geología Ibérica, 1977)
The contact betwaan the Lower Muschelkalk dolostones and the Middle Muschelkalk red shales in the area of Aiguafreda is marked by a carbonate crust of 20-35 centimetres thick, with milimetrie lamination, abundant iron patines and chert rossettes. Ihis crust present remarkable dome and basin structures up to sevaral meters in diameters and 1,5 metres high, and seems not to be relatad with stromatolitic structures neither caliche profiles. The similarity of this crust with the one described in KORNIcKER (1958) and MULTER and HOFEMEISTER (1968) is pointed out.